Role of solvent properties of aqueous media in macromolecular crowding effects. Issue 1 (2nd January 2016) - Ferreira, Luisa A.; Madeira, Pedro P.; Breydo, Leonid; Reichardt, Christian; Uversky, Vladimir N.; Zaslavsky, Boris Y.
Abstract : Analysis of the macromolecular crowding effects in polymer solutions show that the excluded volume effect is not the only factor affecting the behavior of biomolecules in a crowded environment. The observed inconsistencies are commonly explained by the so-called soft interactions, such as electrostatic, hydrophobic, and van der Waals interactions, between the crowding agent and the protein, in addition to the hard nonspecific steric interactions. We suggest that the changes in the solvent properties of aqueous media induced by the crowding agents may be the root of these "soft" interactions. To check this hypothesis, the solvatochromic comparison method was used to determine the solvent dipolarity/polarizability, hydrogen-bond donor acidity, and hydrogen-bond acceptor basicity of aqueous solutions of different polymers (dextran, poly(ethylene glycol), Ficoll, Ucon, and polyvinylpyrrolidone) with the polymer concentration up to 40% typically used as crowding agents. Polymer-induced changes in these features were found to be polymer type and concentration specific, and, in case of polyethylene glycol (PEG), molecular mass specific. Similarly sized polymers PEG and Ucon producing different changes in the solvent properties of water in their solutions induced morphologically different α -synuclein aggregates. It is shown that the crowding effects of some polymers on protein refolding and stability reported in the literature can be quantitatively described in terms of the established solvent features of the media in these polymers solutions. These results indicate that the crowding agents do induce changes in solvent properties of aqueous media in crowded environment. Therefore, these changes should be taken into account for crowding effect analysis.